Evaluation of graffiti art works in greater Kuala Lumpur / David Novak - David, Novak (2016)
‗Graffiti art/Writing‘ consists of four forms: tag, throw-up, piece and character. With the beginning of the 21st century, graffiti art became a constant component of global urban landscapes, including that of Greater Kuala Lumpur (GKL). However, the Malaysian public and academics do not possess a full and detailed descriptive understanding of the content of works produced by the graffiti art culture. Even on a worldwide scale, graffiti art still remains partially unexplored by scholars. Therefore, this present study provides insight into the often ‗hidden‘ content of graffiti art works. The study is using mixed methods of research to investigate the contemporary graffiti art culture‘s visual products. Primary data were collected from fieldwork. Participants are graffiti artists. Qualitative ethnographic research tools, such as interview, photo elicitation and observations form the basis of this study. Quantitative research methods are used for the determination of exact average sizes and partially for the investigation of the content of graffiti art works in GKL. Some personal interviews included a legibility research experiment. Data were also obtained through emails, surveys and distributed questionnaires. The research results show that firstly, graffiti artists evaluate other graffiti art works based on the presence of the graffiti artist‘s works in a public space and on the original ‗style‘ of such works. The aesthetical preferences of 20 graffiti artists identified 28 graffiti art works as aesthetically pleasing (with a 24–44% consensus); the sample consisted of 1003 graffiti art works from GKL (153 tags, 150 throw-ups, 250 characters, 450 pieces). Interesting findings include the facts that graffiti artists consider tags as the building blocks of graffiti art, throw-ups as the technically and stylistically most difficult form of graffiti art, pieces as the most appreciated form of graffiti art, and characters as the most disliked and unpopular form of graffiti art, generally produced to please the public. Secondly, that the research results suggest that the skill to ‗decipher‘ iv illegible letterform-oriented graffiti art works can be acquired; especially through knowledge of graffiti art styles, through knowledge of graffiti artists‘ tag names, and through connoisseurship of individual styles. Thirdly, that the research results demonstrated that the content of themes and motifs present in Malaysian graffiti art works is not only a partial reflection of the local Malaysian culture, but also a reflection of themes and motifs globally present in graffiti art works. Fourthly, that the exact measurements of the dimensions of graffiti art works help to expand our knowledge about graffiti art works. A Major contribution to this study has been the focus on graffiti art works from GKL. The research provides to the uninitiated viewers of graffiti art, insights into the often ‗hidden‘ content of graffiti art works. It is concluded that graffiti art is a dilema manifest in contradictions. Additionally it is proposed that the ‗authenticity‘ of graffiti art works negatively affects the quality of life of people living in cities and that through a more tolerant approach towards graffiti art, as a possible form of public art, the quality of life in cities might be marginally improved.